Crossing the Green Line Between the West Bank and Israel - Allen, Lori (Hagar: Studies in Society and Culture, 2003)
Crossing the Green Line Between the West Bank and Israel By Avram S. Bornstein. Philadelphia: University of Pennsylvania Press. 2002. 170 pp. Birthing the Nation: Strategies of Palestinian Women in Israel By Rhoda Ann Kanaaneh. Berkeley: University of California Press. 2002. 283 pp. Palestine By Joe Sacco. Seattle: Fantagraphics Books. 2001.285 pp. The Object of Memory: Arab and Jew Narrate the Palestinian Village By Susan Slyomovics. Philadelphia: University of Pennsylvania Press. 1998.294 pp.